Modeling Aspects in Optical Metrology VII 2019
DOI: 10.1117/12.2526082
|View full text |Cite
|
Sign up to set email alerts
|

Grazing incidence x-ray fluorescence based characterization of nanostructures for element sensitive profile reconstruction

Abstract: For the reliable fabrication of the current and next generation of nanostructures it is essential to be able to determine their material composition and dimensional parameters. Using the grazing incidence X-ray fluoresence technique, which is taking advantage of the X-ray standing wave field effect, nanostructures can be investigated with a high sensitivity with respect to the structural and elemental composition. This is demonstrated using lamellar gratings made of Si 3 N 4 . Rigorous field simulations obtain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…We have also shown that it outperforms the conventional BO, which has been successfully employed in the reconstruction of parameters in optical metrology. 29,30 We are therefore preparing a publication in which we are investigating the applicability of the BTVO to a comparable problem from optical metrology.…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that it outperforms the conventional BO, which has been successfully employed in the reconstruction of parameters in optical metrology. 29,30 We are therefore preparing a publication in which we are investigating the applicability of the BTVO to a comparable problem from optical metrology.…”
Section: Discussionmentioning
confidence: 99%
“…The is high where we have not evaluated the function or found values close to a minimum of the function. In a previous work [ 27 , 41 ], it was shown that the BO performs much better than other metaheuristic optimization approaches with respect to the computing time needed to find the global minimum. Since BO considers all previous function evaluations, it can be more efficient than other metaheuristic global optimization strategies [ 27 ] and local optimization strategies [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a crucial benefit here, as one model calculation takes several minutes on a standard desktop computer. For a detailed benchmark study of the different optimizer methods in comparison to BO, see [ 27 , 41 ]. For our problem, the BO gives good results in a reasonable amount of time [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BO uses a stochastic model, a Gaussian process, of an unknown objective function to be minimized in order to determine promising parameter values [24,37]. In a previous work [25,38], it was shown that the BO performs much better than other meta-heuristic optimization approaches with respect to the computing time needed to find the global minimum. Since BO considers all previous function evaluations, it can be more efficient than other meta-heuristic global optimization strategies [25] and local optimization strategies [39].…”
Section: Simulation and Optimization Of Fluorescence Intensitiesmentioning
confidence: 99%